Review of the fritillary species systematically close to Melitaea lutko Evans, 1932 (Lepidoptera: Nymphalidae) with analysis of their geographic distribution and interrelations with host plants - Kolesnichenko, Kirill A.; Kotlobay, Anatoly A. (European Journal of Taxonomy, 2022)
This review considers a fascinating, from a zoogeographical viewpoint, group of closely related species: Melitaea lutko Evans, 1932, M. timandra Coutsis & van Oorschot, 2014, M. mimetica Higgins, 1940 stat. rev. and M. shahvarica sp. nov. It is a taxonomical and geographical review of these species, and data on the biology of M. shahvarica sp. nov. and nominate subspecies of M. timandra are discussed. A new species, M. shahvarica sp. nov. from Shahvar Mt. (Iran), and a new subspecies, M. timandra binaludica subsp. nov. from Kuh-e-Binalud Mts (Iran), are described. The specific structure of the group given in previous publications is critically evaluated. Hypotheses about a possible phylogenesis of the study group are provided.